Natural Herbal Supplements – An Assessment Of Their Nutritional Value And Their Phytochemical Constituents - KRUTI PANDYA,; BHAVNA SOLANKI,; KUNAL MANIAR,; NILESH GURAV,; DR SURENDRA BHATT, (International Journal of Pharma and Bio Sciences, 2011)
Nutritional deficiency is almost impossible to avoid in these modern times, thus supplements help us to overcome the nutritional deficiencies. It also helps us to boost our immune system. Nutritional supplements are also useful in getting rid of the toxins that are accumulated in our body. Thus the five natural supplements that are mentioned below are tested for the various parameters that include the basic Quality Control Parameters, the phyto chemical analysis, Microbial Analysis that includes the testing for the presence of pathogens along with the total bacterial and fungal count. It is also tested for the presence of heavy metals in them, followed by Aflatoxin and Pesticide analysis. The Nutritional Value for each of them were determined and reported in the form of mg/capsule. The actives of Licorice Capsule Mucuna Capsule and Triphala Capsule were confirmed by the HPLC method where as that of Shatavari was confirmed by the HPTLC Method.